PERANCANGAN KAWASAN WISATA DI DESA SELOHARJO BANTUL - Wismarani, Yustina Banon; Kirana Analisa, Fabiola Chrisma (DHARMA BAKTI, 2021)
Community service activities at Seloharjo Village aim to encourage the communityto develop a model of the Tourism Village area that has historical potential for tertiaryinstitutions and provides economic prosperity to local communities through the CommunityPartnership-based Design Services Program. Problem solving is used as a method in thedesign process for the development of new products for rural tourism destinations carriedout by universities in terms of providing Design Services. Community service is expected tohelp accelerate the achievement of the Bantul Regency RPJM, and Seloharjo Village. Theoutput of this activity is a masterplan for developing tourist villages with historical potential.The focus of this activity is to solve problems in the rural tourism sector in order to havecompetitiveness and improve the socio-cultural values of the community.